Of Forts and Fairies - Jeffrey Tolbert (Semiotic Review)
This article is an exploration of a particular place in two time periods: the period of my doctoral fieldwork in 2012; and, indirectly, the present of early 2022, a full decade after my initial (and so far only) encounters with the place in question. It is an attempt to think about place both in the immediate, embodied way enabled by conventional in-person ethnographic fieldwork, and in the more remote way demanded by physical and temporal separation. (The latter process, the critical work of relating to a place after the fact, is present mostly in the revisions to the original text, as well as in this introductory section and in the brief postscript.) The location in question, Fairy Fort Farm in Tipperary, Ireland, is a personal chronotope, an index of my time in a place and the subsequent years spent writing and thinking about Ireland without being there. It forms a portion of my own local cosmology, my own understanding of how I relate (and have related) to the world and other people via embodied, emplaced experiences. An important question raised by this exploration of place is the ontological status of a very particular set of “ruins”: the eponymous fairy fort located on the farm. The question of their status as ruins, or possibly an imitation of ruins, unsettled my own understanding of fairy places in Ireland’s supernatural landscape. Although I attempt to center my friend Michael’s interpretation, the question of the fairy fort’s nature remains a compelling one for what it reveals about the central role of experience in the construction of local cosmologies.